Sleep and spa therapies: What is the role of balneotherapy associated with exercise? A systematic review - Castelli, Lucia; Galasso, Letizia; Mulè, Antonino; Ciorciari, Andrea; Fornasini, Francesca; Montaruli, Angela; Roveda, Eliana; Esposito, Fabio (Frontiers in Physiology, 2022)
Balneotherapy and exercise are potential factors influencing sleep through several physiological pathways and relaxing effects. This review aims to assess whether balneotherapy can improve sleep quality in concomitance or not with exercise. The research was conducted on Medline, Scopus, PubMed, Web of Science, and Cochrane Library databases. The current review followed PRISMA reporting guidelines and involves twenty-one articles grouped into four sections based on the characteristics of the balneotherapy protocol: 1.a Balneotherapy – thermal water immersion alone (five studies); 1.b Balneotherapy – thermal water immersion with other spa treatments (six studies); 2.a. Balneotherapy and physical exercise – balneotherapy and out-of-the-pool physical exercise (eight studies); 2.b. Balneotherapy and physical exercise – balneotherapy and in-pool physical exercise (three studies). Apart from healthy or sub-healthy subjects, patients recruited in the studies were affected by fibromyalgia, ankylosing spondylitis, osteoarthritis, musculoskeletal pain, subacute supraspinatus tendinopathy, and mental disorders. Duration, number of sessions, and study protocols are very different from each other. Only one study objectively evaluated sleep, whereas the others used subjective sleep assessment methods. Eight studies considered sleep as a primary outcome and ten as secondary. Sixteen out of twenty-one studies described improvements in self-perceived sleep quality. Thus, balneotherapy associated with other spa treatments and physical exercise seems to be effective in improving self-perceived sleep quality. However, the miscellany of treatments makes it difficult to discern the isolated effects of balneotherapy and physical exercise. Future studies should consider using an objective sleep assessment method and describing the pathways and physiological mechanisms that could provoke sleep changes during balneotherapy treatments.